İstanbul İlinde ABO ve Rh Kan Grupları Dağılımının Analizi - (:unkn) unknown (My University, 2019)
Amaç: Bölgemizdeki kan grubu dağılımını bilmek ve gereksinim halinde bunu pratik ve bilimsel anlamda kullanmayıamaçladık.Yöntemler: 2012-2018 yılları arasında, Kan merkezine kan bağışı amacı ile başvuran 123,900 sağlıklı bireyin kangrupları retrospektif olarak analiz edildi. Kan merkezimize başvuran kişilerin ABO ve Rh kan grupları mikroplakaglütinasyon veya kolon aglütinasyon yöntemleri ile tespit edilmiştir.Bulgular: 123.900 bireyin kan grubu analizi sonuçlarına göre; 47,496 (%38,3) kişi A Rh (+), 36,427 (%29,4) kişi O Rh(+), 16,294 (%13,2) kişi B Rh (+), 7,971 (%6,4) kişi AB Rh (+), 6,793 (%5,5) kişi A Rh (-), 5451 (%4,4) kişi O Rh (-),2,560 (%2,1) kişi B Rh (-), 908 (%0,7) kişi AB Rh (-) olarak saptanmıştır. Rh kan grubu açısından bakıldığında108,188 (%87,31) kişinin Rh (+) olduğu, 15,712 (%12,69) kişinin de Rh (-) olduğu görülmüştür.Sonuç: İstanbul ili demografik olarak Türkiye’nin özetini yansıtmaktadır. Bölgemizdeki kan grubu dağılımı oranlarıTürkiye geneli ve İstanbul bölgesi oranları ile benzerdi. Bununla birlikte diğer bazı bölgelerle farklılıkların daolduğunu gördük. Elde ettiğimiz bulguların kan grupları veritabanı açısından pratiğe ve literatüre faydalı olacağınıdüşünüyoruz.

Objective: We aimed to know the distribution of blood group in our region and to use it in a practical and scientific way if necessary. Methods: Between 2013-2018, blood groups of 123,900 healthy individuals who applied to Marmara University Pendik education and Research Hospital for blood donation were retrospectively analyzed. The ABO and Rh blood groups of individuals who admitted to our blood center were determined by microplate agglutination or colon agglutination methods. Bulgular: According to the results of blood group analysis of 123.900 individuals; 47.496 (38.3%) person a RH (+), 36.427 (29.4%) person a Rh (+), 16.294 (13.2%) person B Rh (+), 7,971 (6.4%) person AB RH (+), 6,793 (5.5%) person a RH (-), 5451 (4.4%) person B Rh (-), 2,560 (2.1%) person B Rh (-), 908 (0.7%) the person was identified as AB RH(-). In terms of Rh blood group,108,188 (87.31%) people were Rh (+) and 15,712 (12.69%) people were RH ( -). Conclusıon: The city of Istanbul is demographically reflecting the summary of Turkey. Blood group Distribution Rates in our region were similar to those in Turkey and Istanbul region rates. However, we have seen that there are some differences with other regions. We think that the findings we get will be useful in practice and literature in terms of blood groups database.
Analysis of Distribution of ABO and Rh Blood Groups in İstanbul Province
Keywords: Genel ve Dahili Tıp